Integration of verified whatapp in the DGT'S public relations business process: Communication channel innovation to improve public trust - Al Hazmi, Raldin Alif (Educoretax, 2025)
This study aims to analyze the use of verified WhatsApp accounts by Indonesia's Directorate General of Taxes (DGT) as an official communication channel to build public trust. The research is motivated by the rise of digital fraud impersonating DGT—especially via WhatsApp—which has weakened public confidence in the tax authority. Using a descriptive qualitative approach, the study collected data through literature review, policy documentation, interviews with MSME actors and DGT officials, and observation of verified WhatsApp account usage. The findings indicate that verified WhatsApp accounts function as strategic credibility signals (signaling), enhance communication effectiveness (media richness), reinforce institutional legitimacy and trust (compliance), and facilitate trust transfer from institution to platform (trust transfer). The verified badge allows the public to distinguish official sources from fake ones, boosting both trust and voluntary tax compliance. The study recommends standardizing the use of verified WhatsApp accounts across all Tax Service Offices (KPP) as part of DGT's digital communications strategy.